Tindak Tutur Mengeluh Bahasa Jepang: Studi Kasus dalam Film Great Teacher Onizuka (2012) - Debby Rosiana Winoto; Bayu Aryanto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This research was conducted to find out the forms of speech act and strategies of complaint in Japanese language. The data were taken from a Japanese drama,